Carfilzomib-dexamethasone vs bortezomib-dexamethasone in relapsed or refractory multiple myeloma by cytogenetic risk in the phase 3 study ENDEAVOR - Chng, Wee Joo; Goldschmidt, Hartmut; Dimopoulos, Meletios A. (Leukemia, 2017)
The randomized phase 3 study ENDEAVOR demonstrated a statistically significant and clinically meaningful improvement in progression-free survival (PFS) for carfilzomib and dexamethasone (Kd) vs bortezomib and dexamethasone (Vd) in relapsed or refractory multiple myeloma (MM). We conducted a preplanned subgroup analysis of ENDEAVOR to evaluate Kd vs Vd by cytogenetic risk. Of 785 patients with known cytogenetics, 210 (27%) had high-risk cytogenetics (Kd, n=97 (25%); Vd, n=113 (28%)) and 575 (73%) had standard-risk cytogenetics (Kd, n=284 (75%); Vd, n=291 (72%)). Median PFS in the high-risk group was 8.8 months for Kd vs 6.0 months for Vd (hazard ratio (HR), 0.65; 95% confidence interval (CI), 0.45-0.92; P=0.0075). Median PFS in the standard-risk group was not estimable for Kd vs 10.2 months for Vd (HR, 0.44; 95% CI, 0.33-0.58; P<0.0001). Overall response rates were 72.2% (Kd) vs 58.4% (Vd) in the high-risk group and 79.2% (Kd) vs 66.0% (Vd) in the standard-risk group. In the high-risk group, 15.5% (Kd) vs 4.4% (Vd) achieved a complete response (CR) or better. In the standard-risk group, 13.0% (Kd) vs 7.9% (Vd) achieved CR. This preplanned subgroup analysis found that Kd was superior to Vd in relapsed or refractory MM, regardless of cytogenetic risk.
Published: 27 December 2016
Gesehen am 13.07.2018
Accepted article preview online 27 December 2016